The Influence Of Financial Flexibility, Managerial Ownership, Firm Size On Capital Structure, And Firm Value On Infrastructure, Utility And Transportation Companies - Asrul Jaya; Djabir Hamzah; Maat Pono; Idayanti Nursyamsi (Publisher Cv. Inara, 2021)
This study aims to analyze the effect of financial flexibility, managerial ownership, and firm size on firm value with capital structure as an intervening variable for infrastructure, utility, and transportation companies. This research was a quantitative study. The data used were secondary data in the form financial statements of infrastructure, utility and transportation companies listed in the Indonesia Stock Exchange during the period 2015-2019. The sample used was a purposive sampling technique consisting of 30 companies infrastructure, utility and transportation. The data were analyzed using path analysis supported by SmartPLS 3.3 software. The results show that financial flexibility has no significant negative effect on the capital structure; managerial ownership has a significant negative effect on the capital structure; firm size has a significant positive effect on the capital structure; financial flexibility has a significant negative effect on firm value; managerial ownership has no significant positive effect on firm value; firm size has no significant positive effect on firm value; capital structure has a significant positive effect on firm value; financial flexibility had no significant effect on firm value through capital structure; managerial ownership has a significant effect on firm value through capital structure; firm size has a significant effect on firm value through capital structure.